Pooh's heffalump movie - Cummings, Jim, 1952-; Nissen, Frank; Fiedler, John, 1925-2005.; Hopkins, Nikita; Walt Disney Home Entertainment (Firm); Buena Vista Home Entertainment (Firm) ([United States] : Walt Disney Home Entertainment ; Burbank, Calif. : Distributed by Buena Vista Home Entertainment, Inc., 2005)
When Roo meets up with a feared Heffalump, he quickly learns an important lesson: they are nothing like what he's been told, and he has much more to gain by befriending Lumpy than fearing him. They strike up a friendship as they spend the day together.
Voices, Jim Cummings, John Fiedler, Nikita Hopkins, Kath Soucie, Ken Sansom.
MPAA rating: G, all audiences admitted.
DVD, region 1.
DVD-ROM minimum system requirements: Windows PC & Macintosh: Adobe Acrobat reader 7.0 or higher, Web browser with Macromedia Flash & or higher plug-in, and a DVD-ROM drive. PC Windows 98SE or later, Macintosh: Mac OS X 10.2. This DVD will not work in a CD-ROM drive.
In English (Dolby Digital 5.1 surround) or French ; closed-captioned.
Keywords: Winnie-the-Pooh (Fictitious character) -- Juvenile drama; Tigger (Fictitious character) -- Juvenile drama; Friendship -- Juvenile drama; French language materials; Video recordings for the hearing impaired